Chitosan Derivatives with Antimicrobial, Antitumour and Antioxidant Activities - a Review - Vinsova, Jarmila; Vavrikova, Eva (Current Pharmaceutical Design, 2011)
Chitosan is a linear polysaccharide with a good biodegradability, biocompatibility, and no toxicity, which provide it with huge potential for future development. The chitosan molecule appears to be a suitable polymeric complex for many biomedical applications. This review gathers current findings on the antibacterial, antifungal, antitumour and antioxidant activities of chitosan derivatives and concurs with our previous review presenting data collected up to 2008. Antibacterial activity is based on molecular weight, the degree of deacetylation, the type of substitutents, which can be cationic or easily form cations, and the type of bacterium. In general, high molecular weight chitosan cannot pass through cell membranes and forms a film that protects cells against nutrient transport through the microbial cell membrane. Low molecular weight chitosan derivatives are water soluble and can better incorporate the active molecule into the cell. Gram-negative bacteria, often represented by Escherichia coli, have an anionic bacterial surface on which cationic chitosan derivatives interact electrostatically. Thus, many chitosan conjugates have cationic components such as ammonium, pyridinium or piperazinium substituents introduced into their molecules to increase their positive charge. Gram-positive bacteria like Staphylococcus aureus are inhibited by the binding of lower molecular weight chitosan derivatives to DNA or RNA. Chitosan nanoparticles exhibit an increase in loading capacity and efficacy. Antitumour active compounds such as doxorubicin, paclitaxel, docetaxel and norcantharidin are used as drug carriers. It is evident that chitosan, with its low molecular weight, is a useful carrier for molecular drugs requiring targeted delivery. The antioxidant scavenging activity of chitosan has been established by the strong hydrogen-donating ability of chitosan. The low molecular weight and greater degree of quarternization have a positive influence on the antioxidant activity of chitosan. Phenolic and polyphenolic compounds with antioxidant effects are condensed with chitosan to form mutual prodrugs.
Keywords: drug delivery